ALEX’S PERCEPTIONS OF HER ROLES IN IKA NATASSA’S DIVORTIARE TRILOGY - Agnes Yosita Atmaja; Jenny M. Djundjung; Meilinda Meilinda (Institute of Research and Community Outreach - Petra Christian University, 2016)
Ika Natassa’s Divortiare trilogy is Metropop genre novels which tell about Alex’s life as a single woman and housewife. Thus, I want to focus on Alex’s way of prioritizing her career as single woman or divorcee and Alex strategies for being a good wife in Ika Natassa’s Divortiare trilogy. I am going to analyze Alex’s life with women’s roles theory related to patriarchal ideology in Indonesia. The first part of analysis discusses Alex’s way to prioritize her career and her reason. The second part explains her strategies for being a good wife in her second marriage. Also, I find that Alex does her work so hard in order to prove that she can survive on her own. I also find that she embraces the traditional feminine roles in order to get a happy marriage. Therefore, she enjoys her life as a married woman rather than a successful single woman.